Marin Alsop conducts Britten's The Young Person's Guide To The Orchestra the Britten-Pears Orchestra for young musicians - Britten, Benjamin (Naxos, 2017)
Like Saint-Saëns's Carnival of the Animals or Prokofiev's Peter and the Wolf, the great English composer Benjamin Britten's Young Person's Guide to the Orchestra is a delightful introduction to classical music, an ideal first foray into a vast and intriguing sonic world. The enchanting work, subtitled Variations and Fugue on a Theme of Purcell, is inspired by a simple Irish dance from a 1695 suite written to accompany the play Abdelazer. Britten shines a light on every facet of the theme and melody, giving each instrument in the orchestra a chance to shine! At the Snape Maltings concert hall in Suffolk, England--near Aldeburgh, where Britten founded the Aldeburgh Festival and lived during his last three decades of life--Marin Alsop conducts the Britten-Pears Orchestra, named for the composer and his partner and collaborator Peter Pears and made up of exceptional young musicians from all over the world. The music is punctuated by brief introductions and interesting interludes by Alsop, who presents each instrument and its place in the symphony orchestra
Keywords: concert; Internet videos